112 Do words matter? investigating how the wording of choosing wisely recommendations influences acceptance among physiotherapists. (20th August 2018) - Zadro, Joshua; Wortley, Sally; Maher, Christopher
Abstract : Objectives: The aim of this study is to explore physiotherapist's preferences for framing of the Australian Physiotherapy Association (APA) Choosing Wisely recommendations, thereby indicating aspects of the wording that could increase acceptance. Method: We will conduct an online discrete choice experiment with ~400 physiotherapist members of the APA who are currently registered and practicing. Participants will indicate their agreement with the initial six APA Choosing Wisely recommendations (strongly agree/agree/unsure/disagree/strongly disagree). Recommendations will then be re-worded according to the following attributes: i) solution (3-level): alternative not provided (1), mentioned at the beginning (2), or mentioned at the end (3); ii) directness (2-level): 'don't' or 'do' vs 'consider avoiding' or 'don't routinely'; and iii) action (2-level): 'don't do' vs. 'do'. Participant will be given 18 scenarios (3 pairwise comparisons for each recommendation) and select which recommendations they would be most willing to follow. Descriptive statistics will identify recommendations participants are most willing to follow. Mixed logit models (using NLOGIT software) will identify attribute levels important for acceptance and the probability a participant will adopt a recommendation. Results: The protocol for this study will be presented at this conference. Conclusions: Choosing Wisely recommendations are intended to reduce low-value care by facilitating open patient-therapist communication. However, the wording of these recommendations could either support or prevent adoption. For example recommendations to 'avoid low-value care' could threaten clinicians and prevent adoption, while recommendations to 'replace low-value care with high-value care' could do the opposite. Further, research has demonstrated that specific recommendations can reduce inappropriate test ordering from physicians managing people with low back pain, while vague recommendations can do the opposite. Globally, over 1200 Choosing Wisely recommendations are published across numerous health disciplines, but no one has investigated how the wording of these recommendations could increase acceptance and adoption. Understanding how the wording of Choosing Wisely recommendations influences acceptance is the first step towards implementation activities to reduce low-value physiotherapy and potentially low-value care across the 200+professional societies with Choosing Wisely lists worldwide.